Postharvest Physiological Studies on the Quality and Shelf Life of Tropical Fruits: A Literature Review - La Oge (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
Tropical fruits possess high economic value but are highly susceptible to quality deterioration after harvest due to ongoing physiological processes. This study aims to review postharvest physiological factors that affect the quality and shelf life of tropical fruits by synthesizing findings from recent literature. Key physiological processes such as respiration, transpiration, ripening, and enzymatic activity are critical in maintaining fruit quality. The findings indicate that effective management of temperature, humidity, controlled atmosphere, and the application of ethylene inhibitors can significantly delay senescence and extend the shelf life of tropical fruits. The novelty of this review lies in its synthesis of recent literature (2020–2024), emphasizing the integration of biological approaches (e.g., plant hormone treatments) and innovative technologies (e.g., edible coatings and smart packaging) to regulate postharvest physiological processes. This review also proposes a synergistic approach combining physiological understanding with technological interventions to optimize the tropical fruit supply chain in developing countries.